Time-Irreversibility and Existence and Uniqueness of Solutions of Problems in Linear Viscoelasticity - Matarazzo, G. (Ukrains’kyi Matematychnyi Zhurnal, 2000)
We study a problem of linear viscoelasticity for the case where the relation between the Cauchy stress and strain tensors is described by a linear integral relation. Theorems on the existence and uniqueness of a solution of the problem are proved.